Tragédia és orvostudomány: Az insania jelensége Seneca Medeájábanés Celsus De Medicinájában - Bán, Katalin (Antikvitás & Reneszánsz, 2018)
In my study, I intend to examine and compare the different forms, manifestations, causes and treatments of insania in Celsus’ De Medicina and in Seneca’s Medea alongside with his prose works. Seneca’s tragedies – just like his prose works – present a deep interest in the psychological states of their characters. One of the best examples is Medea, which is a drama of passion, madness and the destructive forces in the soul. Comparing the tragedy with Celsus’ De Medicina, a nearly contemporary encyclopedic prose text on medical theory and practice, I intend to demonstrate that philosophical and medical understandings of madness interact at some level.